Qualitative Analysis of Enhancing Professionalism and Work Ethic of BPVP Pangkep Apparatus through Data-Based Human Resource Management - Ratnasari, Dewi; Amang, Baso; Hamzah, Muhammad Fadhil (Manunggal Halim Jaya, 2025)
This study examines the improvement of professionalism and work ethic of the apparatus at BPVP Pangkep through data-based human resource management. This qualitative descriptive research employs interview data collected from four informants. The data were analyzed inductively by identifying empirical facts and aligning them with relevant theoretical frameworks. The results reveal that BPVP Pangkep implements data-driven human resource strategies using two primary approaches: employee competency mapping and a digital performance monitoring system. Competency mapping is conducted through assessments of performance, attendance, and periodic evaluations to assign employees according to their expertise and potential. Meanwhile, the digital monitoring system enhances transparency and accountability, encouraging greater discipline and dedication among staff. The findings of this study suggest that, although the implementation of this system shows a promising impact on organizational performance, it still encounters challenges such as limited human resources with adequate digital skills, insufficient technological infrastructure, and resistance to change among employees who are uncomfortable with performance evaluations based on data systems.